PERLINDUNGAN HUKUM TERHADAP DOKTER GIGI DALAM MEMBERIKAN PELAYANAN MEDIS - Ulfany, Riri; Yumanita, Intan; Siregar, Abdul Rahman Maulana (JURNAL KELUARGA SEHAT SEJAHTERA, 2024)
This study examines the legal protection for dentists in medical services, considering the increasing legal risks due to malpractice lawsuits. Dentists play a crucial role in the community's dental and oral health, but legal challenges such as patient complaints and ethical issues can threaten their professionalism. Adequate legal protection is needed so that dentists can practice safely and efficiently. Regulations such as the Medical Practice Law and the Health Law provide a legal framework that protects the rights of dentists while ensuring the quality of service for patients. This research method uses a normative legal approach with a literature study. This study aims to explain the regulations that protect dentists, their legal responsibilities, the challenges they face, and the role of the dispute resolution system. The results indicate the need for increased legal protection so that dentists can operate in a safe and professional environment, as well as recommendations for strengthening access to malpractice insurance and efficient dispute resolution.